Small And Medium Enterprises In The Face Of The Corona Pandemic - benhammou, Fayza; Taibi, Hadjira (جامعة الوادي - University of Eloued, 2022)
الاقتصادية التي خلفتها جائحة كورونا على نشاط المؤسسات الصغيرة والمتوسطة بالجزائر باعتبارها الممثل الرئيسي للقطاع الخاص، والعمود الفقري لاقتصاد الدول النامية والمتقدمة.حيث تمحورت الاشكالية الاساسية في : ما هي مخلفات جائحة كورونا على نشاط المؤسسات الصغيرة والمتوسطة في الجزائر؟ كما هدفت إلى التعرف على خطة الدعم التي وضعتها الحكومة لتخطي المشاكل المالية التي تعرفها هذه المؤسسات وحثها على البقاء ومجابهة هذا الفيروس. This research came to highlight the repercussions of the economic crisis left by the Corona pandemic on the activity of small and medium enterprises in Algeria as the main representative of the private sector, and the backbone of the economy of developing and developed countries. Where the main problem was: what are the remnants of corona pandemic on the activity of small and medium enterprises in Algeria? It also aimed to get acquainted with the support plan set by the government to overcome the financial problems known to these institutions and to urge them to stay and confront this virus.
مقال
Keywords: المؤسسات الصغيرة والمتوسطة ; الاقتصاد ; الانعكاسات ; خطة الإنقاذ، ; الجزائر; Coronavirus (Covid-19) ; small and medium foundation ; economy, reflections ; rescue plan ; Algérie